Coalescence stability of Pickering emulsions produced with lipid particles: A microfluidic study. (October 2018) - Schröder, Anja; Sprakel, Joris; Schroën, Karin; Spaen, Joep N.; Berton-Carabin, Claire C.
Abstract: In the quest to find approaches to prepare food grade Pickering emulsions, we studied the formation and stability to coalescence of colloidal lipid particle (CLP)-stabilized emulsions within a cross-flow microfluidic device. We show that the particles can either stabilize or destabilize the emulsions depending on the particle adsorption rate versus droplet formation rate, and on the resulting surface coverage when the droplet is formed. At low surface coverage, when droplet formation is significantly faster than adsorption, CLPs have a destabilizing effect as incomplete surface coverage leads to droplet-droplet bridging. At high surface coverage, the dense particle layer results in an effective barrier against droplet coalescence, resulting in physically stable emulsions. The observed non-monotonic dependency of emulsion droplet stability on surface coverage of CLP-stabilized emulsions is in stark contrast to what is observed for conventional surfactant-stabilized emulsions, and thus should be taken into account for the rational design of Pickering emulsions. Highlights: The coalescence of emulsion droplets stabilized by colloidal lipid particles was studied using a microfluidic device. The tendency of emulsion droplets to coalesce strongly depends on particle coverage. Particles have a destabilizing effect on emulsion droplets at low surface coverage due to droplet-droplet bridging. Droplet coalescence can be prevented at sufficiently high surface coverage, resulting in physically stable emulsions.